Aroma Profile Discrimination of Coffees and Industrial Blends According to the Chromatic Value - Rodrigues, Carla Igreja (2013)
In the present work, static headspace solid phase microextraction using carboxen/polydimethylsiloxane polymeric fibre (HS-SPME(CAR/PDMS)) followed by gas chromatography-mass spectrometry (GC-MS), revealed the best analytical performance to characterize the aroma profile of coffees and industrial blends with different chromatic values (64.9, 70.6, 75.3, 86.1 and 89.6). The most relevant classes of aroma compounds founded were pyrroles, ketones, pyrazines, furans, phenolics, pyridines, alcohols and acids, independently of the roasting degree. By combining the analytical methodology with principal component analysis (HS-SPME(CAR/PDMS)/GC-MS/PCA), important aroma compounds such as 2-furancarboxaldehyde, 2-furanmethanol and acetic acid, allows to discriminate the different roasting degrees, from light (chromatic value 89.6) to dark (chromatic value 64.9) roast. The proposed analytical approach may help to build aroma profile databases to a better evaluation of coffee blends quality, and in controlling the industrial roasting processes.